Alasdair Macintyre:: A Critic Of Modernity - Sioufa, Basiliki (Dia-noesis: A Journal of Philosophy, 2024)
The article provides an account of some aspects of Alasdair MacIntyre’s moral and political critique of liberal modernity. It reconstructs major concepts of his moral theory, i.e. his concept of the virtues, of a ‘practice’, of a ‘narrative unity of a human life’, of ‘external’ and ‘internal’ goods, and of a moral ‘tradition’. It then gives an account of his project of a politics of local community. The article argues that MacIntyre’s critique is a Thomist moral and political project, which understands the relation of the individual to the community in ways difficult to reconcile with the contemporary conception of the person, of individual rights and of the relation of the individual to the state.